Faktor Faktor Yang Mempengaruhi Sopir Truk Dengan Ims Untuk Test Hiv Di Wilayah Pantai Utara Jawa Tengah - Fajar Surahmi; Kurniati Puji Lestari; Sri Endang Windiarti (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
As a truck driver, is a consequence of having to travel a long and tiring from the eastern end of Java samapai Jakarta. This trip is done regularly and over 3 profinsi the area of Central Java, West Java and DKI Jakarta entered. Through out the rest of the crew truck where there are female sex hawkers (WPS) which directly or indirectly coloring transactional sex to the crew's truck. Supply and demand is very high in the area, so the issue of sexual behavior to be important to convey. Survey conducted by BPS and the MOH in this group in 2007 issued 5% of data that this truck crews have an STI. Research purposes Mendidkripsikan factor - factor that affect truckers IMS for HIV test. This research will be conducted descriptive analytic cross sectional design. Research places like truck stops Tegal, Batang, Pekalongan, Kendal, Semarang, Demak and Apex. Sample population and sample work was taken by sampling the total sampling technique, the sample size of approximately 47 truck drivers. Analysis of test results using ststistik with chi-square test showed that there is one variable significantly affect the HIV test is a truck driver attitudes towards HIV testing behavior, with a significance level of 5% is obtained p value 0.009, independent Variable most predominant predictor truck driver HIV test is a truck driver attitudes towards HIV testing with significant value of 0.013. Attitudes towards HIV testing truckers who do not support the Wald p value = 6,237 and the value adjusted OR or exp (B) 0, 117 means that the truck driver attitudes towards HIV testing do not support having 0.143 times the risk for contracting HIV. This research should continue because the ground was very poor, so the results of the present invention can determine the appropriate intervention to increase awareness of truck drivers to maintain her health